The morpheme le in Northern Sotho : a linguistic analysis - Sejaphala, Makoma Doncy (My University, 2010)
This study focuses on the morpheme le in Northern Sotho. It is sometimes confusing to establish the correct semantic function which the morpheme le expresses; and also to classify it into a certain word category. This study suggests the morphological features which the morpheme le bears in terms of its word categorization. The morpheme le in Northern Sotho can be used as a conjunction, a demonstrative pronoun, an agreement, a preposition, a copulative, an adverb and a complement as well. It is suggested in this study, ways of identifying the semantic function of the morpheme le in various contexts. This study reflects that the morpheme le in Northern Sotho can be used to denote: possession, accompaniment, location, additive focus, existentialism and honorifics.
Thesis (M.ED.) --University of Limpopo, 2009.
Keywords: morpheme le; Northern Sotho; morphological features